Survey of Slum Housing Characteristics Using Drones: An Experiment in the Alto das Pombas Community, Salvador de Bahia/Brazil - Gomes Joice Genaro; Pedrassoli Julio Cesar (Quaestiones Geographicae, 2021)
Since the approval of the Brazilian Federal Technical Assistance Law, whose objective is to guarantee adequate technical assistance to the residents of poor areas to improve their homes, several municipalities have implemented programs, not always successful, to improve housing in slums. Aiming to subsidize these programs implementation workflow, the present paper analyses use of drones as a tool to gather information about the physical characteristics slum households in Salvador de Bahia city, Brazil. As an experiment we flight over a single census sector within the Alto das Pombas slum, and after image processing we extracted and organized the collected data, extracting the possible information that could be applied to identify and quantify the most precarious houses that could be prioritized from a health improvement perspective. We conclude that many of the necessary data needed, on the urbanistic scale in Brazilian slums, can benefit from drone photogrammetry at low cost and fast execution.